Deflazacort and Nevridol 800 to prevent acute carpal tunnel syndrome in adult distal radius fractures - Luigi Meccariello (Medicinski glasnik, 2023)
Aim: Acute carpal tunnel syndrome (ACTS) is a well-recognized and common condition following a distal radius fracture. The aim of this study was to test deflazacort associated with Nevridol®800 or deflazacort alone in order to prevent moderate or severe ACTS after the distal radius fracture in adults. Methods: Sixty-four patients suffering from extraarticular wrist fractures were divided into three groups. The first group (n=26) was treated by plaster cast. The second group (n=20) was treated by cast and deflazacort (heterocyclic glucocorticoids prodrug belonging to the class of oxazoline steroids) 30 mg/day for 15 days. The third group (n=18) was treated by cast and deflazacort 30 mg/ day for 15 days + Nevridol (food supplements) 800 mg a day for 40 days. The criteria to evaluate the patients were: the complication of ACTS, the duration of symptoms, the functional results were evaluated according to The Disabilities of the Arm, Shoulder and Hand (DASH) life correlated with wrist function by the Short Form 12 Health Survey (SF-12), and positive Tinel and Phalen test. The correlation between ACTS signs and volar tilt in the latero-lateral at X-rays in the three studied groups was assessed. The endpoints were set on 7 days, 15 days, 1 months, 2 months and 3 months after a trauma. Results: In the first group, 12 of 26 (46.15%) and the second group 7 of 20 (35%) patients suffered from ACTS, while in the third group only two of 18 (11%) patients (p=0.033). After 3 months of treatment, the third group had better results in DASH (p=0.034), SF-12 (p=0.044), Tinel (0.045) and Phalen (0.048) tests. Conclusion: Deflazacort associated with Nevridol 800 may reduce the prevalence of postoperative median nerve dysfunction.
Keywords: adjunctive therapy; alpha lipoic acid; borage oil; nerve dysfunction